The animal feed industry for developing countries - Koenig Horst R
Animal feed production for developing countries-covers (1) animal feed industry as a development factor: the utilization of agro-industrial by-products, use of agricultural residues (2) large-scale production of compound animal feed, market-orientation, feed raw materials, storage, automation, computerization (3) rural industrial production of animal feed (4) special feedstuffs and feed ingredients: oil cakes, oils and fats, rubber seed press cakes, cassava, molassses (5) economic feasibility, storage, quality control.
Keywords: Developing countries; Feed production; Industry; Rubber seed